RELIGIOUS AND PHILOSOPHICAL FOUNDATIONS OF MAKHTUMKULI’S ARTISTIC-CREATIVE AND SPIRITUAL-MORAL HERITAGE - Rahimova Aziza Davronbekovna (EPRA International Journal of Research and Development (IJRD), 2022)
This article illustrates the Makhtumkuli’s views, which the world itself has a reality of ideal aspiration, so that the image of the beloved reflects the inner essence of absolute beauty, and that the formation and development of the human soul is a reality, not a frozen reality.